Telephone ted: ladybird picture stories - Stimson, Joan; Mitchley, Richard Pertwee, Jon Campbell, Sharon Francis, Jan (Ladybird Books London, 1996)
Charlie has started school and poor Ted is left sitting at home. It's not much fun being a teddy on your own and so, when the telephone starts to ring, Ted gets excited - maybe it's someone he can talk to. But no one can understand his gruffly growl until Brenda Bear from across the road calls.